VALIDASI METODE TES STRIP (á-Globin Strip Assay) TERHADAP METODE PCR RUTIN DALAM MENDETEKSI MUTASI THALASSEMIA ALFA TIPE SOUHTEAST ASIA (--SEA) - Puspitasari, S -; Supartini S -; Margaretha, I.N - (Bionatura, 2012)
The aims of this research was to give information as material study to the test strip (α-Globin StripAsay) and therefore provide an alternative or replacement method in α-thalassemia mutation detection. DNA produced from three DNA isolation methods (puregene, chelex and spin micro) were used as a geneticmaterial for diagnostic test of strip test method in detecting two α-globin gene deletion SEA type (--SEA), the common α0-thalassemia (severe type) compare to PCR routine methods as a gold standard.The method used in this research was an analytical descriptive. Parameters measured were value of sensitivity and spesifisity of strip test on the three DNA template. The result showed all DNAs give 100% of sensitivity value in detecting two α-globin gene deletion SEA type. The specificity value was94,74 ; 31,58 and 84,21 % from DNA isolated using puregene, chelex and spin micro DNA extraction methods, respectively.Key words : Thalassemia α, DNA, strip test, sensitivity, specificity.